2015
DOI: 10.1093/jme/tjv108
|View full text |Cite
|
Sign up to set email alerts
|

Myiasis of the Tracheostomy Wound Caused bySarcophaga(Liopygia)argyrostoma(Diptera: Sarcophagidae): Molecular Identification Based on the Mitochondrial Cytochrome c Oxidase I Gene: Fig. 1.

Abstract: Wound myiasis is the infestation of open wounds of mammalian hosts caused by larvae of various species of flies. This kind of myiasis can be a serious problem for immobilized patients with open wounds. Here, we identify a dipteran larva found in the tracheostomy wound of a child affected by a severe spinal muscular atrophy. The collected larva was dissected and microscopically analyzed. DNA was extracted from part of the larva and used for the molecular identification. A 487 bp fragment, including part of 5.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…The robustness of the coxI gene as a diagnostic marker to lay the groundwork for identification of these three species of Sarcophaga has been demonstrated [ 21 , 26 ]. Sarcophaga argyrostoma has been identified using a coxI sequence in an elderly patient with an external ophthalmomyiasis (with 97% identity) [ 6 ] and very recently in a tracheotomized child's surgical wound (with an identity of 100%) [ 8 ]. In the present study, the involvement of S. argyrostoma in the wound myiasis is confirmed with 99% identity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The robustness of the coxI gene as a diagnostic marker to lay the groundwork for identification of these three species of Sarcophaga has been demonstrated [ 21 , 26 ]. Sarcophaga argyrostoma has been identified using a coxI sequence in an elderly patient with an external ophthalmomyiasis (with 97% identity) [ 6 ] and very recently in a tracheotomized child's surgical wound (with an identity of 100%) [ 8 ]. In the present study, the involvement of S. argyrostoma in the wound myiasis is confirmed with 99% identity.…”
Section: Discussionmentioning
confidence: 99%
“…This is the third case in Europe [ 4 , 8 ]. Cases of myiasis caused by Sarcophaga species are apparently few, but it must be underlined that cases of myiasis often remain unrecorded or that, more frequently, identification is partial, that is, at genus level [ 27 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7] In a massive internet search using PubMed/Medline services, authors could find only 3 cases reported in children on the cited subject. 6,8,9 Myiasis is classified as specific (obligate), semi-specific (facultative), and accidental (pseudomyiasis). 2 Open wounds and bodily orifices that emit odors of natural secretions are major factors in susceptibility to myiasis, as they provide a favorable environment for attraction and oviposition of flies.…”
mentioning
confidence: 99%